Protective Effects of Borago officinalis (Borago) on Cold Restraint Stress-Induced Gastric Ulcers in Rats: A Pilot Study - Di Cerbo, Alessandro; Carnevale, Gianluca; Avallone, Rossella; Zavatti, Manuela; Corsi, Lorenzo (Frontiers in Veterinary Science, 2020)
Stress is a typical body’s natural defense to a generic physical or psychic change. A specific linking mechanism between ulcer onset and psycho-physical stress prolonged exposure has been reported. We decided to investigate the possible effects of Borago officinalis L. (Borago) in preventing physical (stress)-induced gastric ulcers in a rat model. Eighty male Sprague-Dawley rats were randomly divided into 16 groups, pre-treated with a control solution, omeprazole (20 mg/kg), Borago methanolic extract (25, 50, 100, 250 and 500 mg/kg), Borago organic extract (50, 100, 250 and 500 mg/kg), Borago aqueous extract (5, 10, 20, 30 and 40 mg/kg) and D(-)-2-Amino-5-phosphonovaleric acid (AP5) (25 mg/kg), kept in stressful conditions such as water immersion and restraint-induced stress ulcers. The animals were sacrificed and their stomach scored for the severity and the number of gastric ulcers. Methanolic extract (500 mg/kg) significantly reduced both ulcer parameters (***p < 0.001 and **p < 0.01, respectively). Aqueous and organic extract significant decreased severity score at 5 and 10 mg/kg to (**p < 0.01 and ***p < 0.001, respectively), and at 250 and 500 mg/kg (***p < 0.001), respectively; while gastric ulcers’ number resulted significantly reduced only at 10 and mg/kg (*p < 0.05), and at 500 mg/kg (**p < 0.01), respectively. On the other hand, aqueous extract significantly increased the mucosal gastric content of cAMP (*p < 0.05) and NR2A and NR2B subunits (*p < 0.05 and **P < 0.01, respectively) at 5 mg/kg. Organic extract showed also a significant cytotoxic effect at 500 and 1000 mg/kg with a 3T3 cell viability reduction of 43.6 % (**P < 0.01) and 92.1% (***P < 0.001), respectively. Borago aqueous extract at 10 mg/kg could be considered as a potential protective agent against stress-induced ulcers and it is reasonable to possibly ascribe such protective activity to a modulation of the NR2A and NR2B subunits expression.